2012
DOI: 10.1016/j.msea.2012.04.076
|View full text |Cite
|
Sign up to set email alerts
|

Effect of manganese content and microstructure on the susceptibility of X70 pipeline steel to hydrogen cracking

Abstract: The influence of composition and microstructure on susceptibility to hydrogen induced cracking (HIC) was investigated in high strength pipeline steels, with Mn contents of 1.2% (standard, X70), and 0.5% (medium, MX70). The HIC resistance of the simulated coarse grained heat affected zone microstructures and normalized X70 transfer bar was also investigated. Notched and fatigue pre-cracked samples were charged with hydrogen prior to three point bend tests. The conditional fracture toughness JQ was determined. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 118 publications
(58 citation statements)
references
References 49 publications
3
54
0
1
Order By: Relevance
“…Due to the sample geometry of the tensile test pieces, the volume containing centreline segregation was removed, whereas it was present in the TPB samples. Unlike S-X70, the centreline region of M-X70 strip contained elongated MnS stringers with some blocky inclusions among these stringers, as well as a higher number density of oxides [27]. These microstructural features have been reported by Domizzi et al [37] to promote HICC and they could, therefore, have contributed to the higher incidence of HICC in the TPB tests of M-X70.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Due to the sample geometry of the tensile test pieces, the volume containing centreline segregation was removed, whereas it was present in the TPB samples. Unlike S-X70, the centreline region of M-X70 strip contained elongated MnS stringers with some blocky inclusions among these stringers, as well as a higher number density of oxides [27]. These microstructural features have been reported by Domizzi et al [37] to promote HICC and they could, therefore, have contributed to the higher incidence of HICC in the TPB tests of M-X70.…”
Section: Discussionmentioning
confidence: 78%
“…In all cases of hydrogen atmosphere testing, partial or complete brittle fracture by quasi-cleavage was observed. HICC associated with inclusions and other stress-concentrating defects would be required to initiate and extend cracking by quasi-cleavage, which dominated the fracture mode of the hydrogen-charged samples that were tensile tested at 25 o C. Electrolytic charging of the same steels [27] clearly established the presence of hydrogen cracking throughout the strip cross-sections and it is therefore reasonable to expect the presence of cracking in regions surrounding the final crack surface in the present case. However, the presence of sub-critical cracks was not confirmed because it was not considered to have a significant bearing on the main findings of the work.…”
Section: Fractographymentioning
confidence: 74%
See 1 more Smart Citation
“…Recent studies involving precipitate analysis of the two steels using scanning electron microscopy [51] have shown that the medium Mn steel exhibits a significantly larger number density of precipitates and inclusions. Most of these precipitates were found to be complex carbonitrides of Ti and Nb having an average diameter of 0.8  0.8 m.…”
Section: Comparison Of Standard Mn and Medium Mn Stripmentioning
confidence: 99%
“…O efeito simulado da segregação é apresentado na Figura 8. É evidente que, quando a segregação é levada em conta, o enriquecimento interdendrítico em Mn e S leva a precipitação de MnS no final da solidificação, criando regiões concentradas neste sulfeto, muito desfavoráveis a resistência a HIC [41]. A adição de Ca, além de garantir a lingotabilidade, leva a formação de CaS, considerado o melhor sulfeto, nestes aços [2,6].…”
Section: Figuraunclassified